The effects of roasting on antioxidant and anticancer activities of fermented Hass avocado seeds - Zhao, Zhiyu; Hamid, Nazimah; Qian, Liuyi; Gutierrez-Maddox, Noemi; Kam, Rothman; Kantono, Kevin; Wang, Kelvin; Lu, Jun; Le, Thao T. (Frontiers in Food Science and Technology, 2022)
Avocado by-products present a waste issue for cold-pressed avocado oil processors in New Zealand. The avocado seed contains many extractable compounds that are beneficial to health. This work aims to evaluate the effects of roasting fermented avocado seed to produce a food ingredient with beneficial antioxidant and anticancer properties. Avocado seeds were subjected to natural fermentation and inoculated fermentation with either Lactobacillus plantarum or kefir. The fermented samples were evaluated in terms of total plate count values of lactic acid bacteria acetic acid bacteria and yeasts. The number of microorganisms increased significantly (p < 0.001) over the 7 days of fermentation for all samples. Fermentation with L. plantarum resulted in significantly (p < 0.05) higher total phenolic content (TPC) and antioxidant activities compared to kefir and naturally fermented samples. The fermented avocado seeds were further subjected to roasting to yield a shelf-stable dried powder. Roasted samples fermented by L. plantarum had significantly (p < 0.001) higher total polyphenolic content and antioxidant capacity (CUPRAC and Ferric Reducing Antioxidant Power assays) compared to kefir and naturally fermented samples. The avocado seed powder showed the best inhibition effect on Hep G2 followed by the MDA-MB-231 and MCF-7 cancer cell lines. The roasting conditions for optimal antioxidant and anticancer activities were determined to be at 127°C for 24.7 min. This study demonstrated that fermentation of avocado seeds in combination with roasting yielded a powder with good antioxidant and anticancer activities, which can potentially be incorporated into food for added health benefits.